Production of glucose from banana stem waste using Strain A - Nurhasiken, Raman (2010)
Fermentable sugars are the largest feedstock available to support bio-based chemicals industry. Growth of a bio-based chemicals industry will depend on production of fermentable glucose. Production of this glucose from banana stem waste can help to reduce the environmental problem. This study is studying glucose production from banana stem waste using Strain A. While, the purposes of this study are to study the effect of organic loading rate (OLR) during production of glucose, to optimize the glucose production using banana stem waste and to study suitability of banana stem waste as substrate for glucose production using Strain A. Organic loading rate for this study is determined by using Design Expert. The banana stem waste is used as substrate and contains 27.64% of total solid.The experiment used fed batch fermentation. The fermented mixture were removed 50 mL and after that, 50 mL of fresh substrate is added back to shake flask. This experiment be done for eight runs with different values of OLR (g L-1 d-1); 5, 11.25, 17.5, 23.75, and 30.The experiment was also carried out for 30 days. The concentration of glucose is analyzed using DNS assay. The optimization of glucose production is determined using Design Expert through One Factor Analysis. The increasing yield of glucose is affected by decreasing the value of OLR. The optimum OLR is 5 g L-1 d-1 was produced the maximum of yield of glucose and it is 0.0734 g/g substrate. The banana stem waste is suitable substrate in production of glucose using biological hydrolysis process and Strain A.